Chapter La cittadinanza tra soggettività singolarista e crisi della rappresentanza - D'Andrea, Dimitri (Studi e saggi, 2023)
The liberal democracies of the West are experiencing a process of slow but constant and apparently unstoppable degradation. The main thesis of this contribution is that the primary reason for this degradation must be identified in the jamming of the representative mechanism and in the incapacity of democratic politics to stage transparent, recognizable and realistic conflicts on significant dimensions of social life and to present ideas of different and probable futures. Pulverized by complexity and differences, society and the future have become unrepresentable. Saturation of the world and global interdependence, on the one hand, assembled identities, belongings without transcendence and individualization of meanings, on the other, produces a need for immediacy, for political and social disintermediation that is increasingly less compatible with the functioning of representative democracy and with its privileged if not exclusive incardination within the framework of the nation-state. The outcome is, therefore, that of a structural misalignment between configurations of subjectivity and institutional arrangements. Underlying the troubles of modern democracy is the increasingly evident gap between individuals as they really are (became) and individuals as they should be in order for political institutions to function adequately.